Lichtenstein repair in a 50year old known hypertensive woman with right inguinal Hernia - Azeez, Ismaheel A.; Lasisi, Jamiu A; Adebusoye, Lawrence A; Yusuf, Banke I. (Jour Med Resh and Health Sci, 2019)
Hernias by themselves may be asymptomatic, but nearly all have a potential risk of being strangulated. Inguinal hernias are usually caused by a congenital defect which occurs as a weakness in the inguinal canal manifesting after injury, pregnancy or aging. This was a case of a 50-year-old woman known hypertensive who presented with right inguinal swelling of two years duration. The swelling was painless and had increased progressively in size. Examination showed the abdomen to be full, moved with respiration, no area of tenderness, liver and spleen were not enlarged and the kidneys were not ballotable. There was a palpable and visible cough impulse in the right inguinal region. She was managed for hypertension and the hernia by Lichtenstein repair. She was also being managed for hypertension. The Lichtenstein repair which is a tension-free repair was found to be associated with a lower incidence of recurrence, pain, numbness, and discomfort and so it is a better option than the traditional Bassini repair. However, despite evidence of better outcomes in Lichtenstein repair, most Physicians especially in Nigeria have not adopted this in their practice. Therefore, there is a need for more publications on this approach of herniorarrhaphy.